Modulation of membrane permeability by carbon dioxide. Issue 5 (3rd September 2019) - Zhang, Hong; Shao, Xueguang; Dehez, François; Cai, Wensheng; Chipot, Christophe
Abstract : Promoting drug delivery across the biological membrane is a common strategy to improve bioavailability. Inspired by the observation that carbonated alcoholic beverages can increase the absorption rate of ethanol, we speculate that carbon dioxide (CO2 ) molecules could also enhance membrane permeability to drugs. In the present work, we have investigated the effect of CO2 on the permeability of a model membrane formed by 1‐palmitoyl‐2‐oleoyl‐sn‐glycero‐3‐phosphocholine lipids to three drug‐like molecules, namely, ethanol, 2′, 3′‐dideoxyadenosine, and trimethoprim. The free‐energy and fractional‐diffusivity profiles underlying membrane translocation were obtained from μs‐timescale simulations and combined in the framework of the fractional solubility‐diffusion model. We find that addition of CO2 in the lipid environment results in an increase of the membrane permeability to the three substrates. Further analysis of the permeation events reveals that CO2 expands and loosens the membrane, which, in turn, facilitates permeation of the drug‐like molecules. © 2019 Wiley Periodicals, Inc. Abstract : In the present work, modulation by CO2 of the membrane permeability to drugs has been investigated combining free energy and diffusivity calculations within the framework of the fractional solubility‐diffusion model of permeation. The results indicate that CO2 loosens the membrane, thereby increasing the permeability to drugs. The present contribution provides a newfangled view that the thermodynamics and kinetics of permeation events can be modulated by gaseous species.